A review on the origin of multidrug-resistant Salmonella and perspective of tailored phoP gene towards avirulence. (October 2020) - Gangathraprabhu, Balasubramani; Kannan, Suganya; Santhanam, Geethanjali; Suryadevara, Nagaraja; Maruthamuthu, Murugan
Abstract: Salmonellosis continues to remain a health problem as the causative organism Salmonella spp. developed resistance to many of the antibiotics. As per World Health Organization (WHO), it is estimated that enteric fever, accounts for almost 16 million cases annually and over 600, 000 deaths worldwide. Recent data revealed that the multi-drug resistance (MDR) rate of enteric fever was as high as 70% in Asian countries, as compared with the overall reported incidence of 50%. Emergence of MDR typhoid fever demands the use of newer antibiotics which also not offer promising effect in recent days. Effective antimicrobial therapy is required to control morbidity and prevent death from typhoid fever. The studies on PhoP/Q regulation revealed it as a best-characterized transcriptional regulation; a two-component system required for Salmonella pathogenesis which controls the expression of more than 40 genes. The PhoP DNA binding proteins possess positively charged amino acids such as arginine, lysine and histidine which present in the DNA binding site. Prevention of PhoP binding in phoP box may ultimately prevent the expression of many regulatory mechanism which plays vital role in Salmonella virulence. Deepness study of PhoP protein and various mutation swots may offer effectual controlling of MDR Salmonella . Highlights: A very first review on the collective information including gene therapy for MDR Salmonella spp. Compare to chemical inhibitors, gene therapy may more specific and not disturb or kill commensal. Since MDR organisms having potent effluxing system and enzyme mediated degradation, chemical compounds unable to give promising effect for long time. The sum target is to block the phoP box which is highly required for PhoP protein to drive pathogenic gene expression. Tailored phoP may be the successful opening for effective therapy to control the infections.